UJI AKTIVITAS ANTIOKSIDAN DAN ANTIBAKTERI EKSTRAK DAUN Ricinus communis L (JARAK KEPYAR) - Julia Sarfina; Nurhamidah Nurhamidah; Dewi Handayani (ALOTROP, 2017)
This study aims to determine the antioxidant activity of jarak kepyar’s  leaf extracts (Ricinus communis L.) and to determine of the fraction the growth of Erwinia carotovora. Jarak kepyar’s leaf extracted by maceration method using ethanol and fractionated using n-hexane and ethyl acetate. Antioxidant test using DPPH (1,1-diphenyl-2-picrylhydrazyl) with various concentrations of 125 ppm, 100 ppm, 75 ppm, 50 ppm, 25 ppm, 15 ppm and 5 ppm. Antibacterial test conducted on the active fractions as antioxidants using paper disc method and variations in the concentration of 1000 ppm, 500 ppm, 250 ppm, 125 ppm, 62.5 ppm. Phytochemical test results jarak kepyar’s leaf contain secondary metabolites are alkaloids, flavonoids, phenols and terpenoids. The test results demonstrate the antioxidant activity of ethyl acetate fraction is very strong as an antioxidant with IC50 values of 5.4 ppm and a strong ethanol fraction categorized as antioxidants IC50 of 99.8 ppm. Antibacterial test results showed inhibition of the leaf fraction of  jarak kepyar’s (Ricinus communis L.) against Erwinia carotovora categorized weak growth in ethanol fractions with inhibition zone diameter of 4 mm and being in ethyl acetate fraction with a diameter of 5 mm